EPIDEMIOLOGICAL ASSESSMENT OF FELINE PANLEUKOPENIA AMONG DOMESTIC CATS IN AND AROUND BENGALURU - H.J. Apoorva; V.S. Lathamani; P.T. Ramesh; M.P. Veena; R. Sudharani; Shivaraj B. Murag (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Feline panleukopenia (FPL) is an acute, highly contagious viral disease of cats characterized by profound leukopenia, enteritis and high mortality in susceptible populations. This study evaluated the incidence of FPL in domestic cats presented to the Veterinary College Hospital, Hebbal, Bengaluru, using clinical, hematological, biochemical, and molecular diagnostic approaches. A total of seventy-six suspected cases and six healthy controls were screened. The causative agent, Carnivore protoparvovirus 1, was confirmed using polymerase chain reaction (PCR) and rapid immunochromatographic (IC) testing. Results revealed that 82.89% of suspected cats were PCR-positive, with the highest prevalence in unvaccinated, outdoor, non-descript cats aged three to six months. Epidemiological factors such as immunization status, housing type, deworming, diet, and early maternal nutrition significantly influenced disease occurrence. The findings emphasize the importance of vaccination, biosecurity, and early preventive care in controlling FPL outbreaks.